Factors associated with clinical, immunological and virological responses in protease-inhibitor-experienced brazilian children receiving highly active antiretroviral therapy containing Lopinavir-Ritonavir - Machado,Daisy Maria (2007)
This study evaluates clinical, virological and immunological responses to antiretroviral (ARV) therapy based on Lopinavir/ritonovir (LPV/r) in previously protease -inhibitor-experienced children. The study included 29 Brazilian children (median age = 5.91 years) who had failed previous ARV therapy and had begun a regimen based on LPV/r. At 12 months follow-up, a good virological response to LPV/r therapy was defined as achieving an undetectable viral load or as a decrease in plasma HIV RNA levels to > 1 log. A good immunological response was defined as an increase in CD4+ cell count from baseline sufficient to attain a better CDC immune stage classification. The number of infectious episodes 12 months before and 12 months after beginning LPV/r was assessed. Sixteen (55.2%) and 19 (65.5%) of 29 patients exhibited good virological and immunological responses, respectively. Baseline CD4+ values (>500) predicted both virological and immunological responses (p<0.05). Older children were less likely to develop an immunological response (p<0.001) than younger children. Nine children receiving 3 ARV drugs plus LPV/r showed an immunological response (100%) compared to 10/20 (50%) children receiving 2 drugs plus LPV/r (p=0.01). A lower number (n<5) of infectious episodes was noted after 12 months follow-up in children using the LPV/r regimen (p=0.006). There was a positive correlation between children whose baseline CD4+ values were greater than 500 cells/mm³ and virological responses. Although virological responses to therapy were seen in about half the children (55.2%), the use of HAART containing LPV/r provided clinical and immmunological benefits.